'Keeping my mind strong': enabling children to discuss and explore issues relating to their perceptions of positive mental health through the arts. (November 2016) - O'Neill, Marie Therese; Moore, Kevin David
Background: The ramifications of mental ill health are enduring and potentially disabling. This research study focuses on using art to explore children's understanding and awareness of mental health issues. Aims: To explore the medium of 'drawing' as a method of communication by young people for expressing feelings and thoughts about what keeps their minds strong and what makes them happy as children. Method: Arts-based research was used as a primary mode of inquiry to collect data and conduct analysis. Sample: A total of 16 schools participated, with 10 from the primary school sector (children aged 5–11 years) and six from the post-primary sector (11 + to 18 years). A total of 358 posters were submitted. Findings: Emergent themes suggested the existence of the awareness of stigma, which accompanied mental health issues and social isolation. In addition, perceptions of what makes children happy were also apparent, for example, family and friends. Similarities existed in the relationship between genders of a similar age group, and some differentiations presented between primary and post-primary educational sectors. Implications: Arts-based research offers children an opportunity to recognise and express their feelings. Early identification of a child's mental health problems may enable mental health nurses to engage in early intervention strategies to promote positive health functioning.